Pemberdayaan Perempuan dalam Realisasi Edukasi Pasar Agro di Kecamatan Mijen - Restu Afrianto; Ika Yunita Ratnasari; Yuyun Safitri Cahyani Arumsari; Ratih Pratiwi; Sunarto Sunarto (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Sumbersari Village, Wonolopo Subdistrict, Mijen District is a unique village with a cool climate that has a social, economic status with the second high prevalence of stunting in the city of Semarang with a percentage (13.75%) and Natural Resources which have great potential to improve the quality of life by creating an environment that better in economic life. The importance of this village empowerment effort is to support government programs that are included in the 17 Sustainable Development Goals. This community service program seeks to ensure food security and better nutrition to support inclusive, sustainable and productive economic growth to create good jobs for the community. The Independent Real Work Lecture Program at Wahid Hasyim University is one of the implementations of healthy food and supports sustainable agricultural programs in villages, partnering with the community, by using a system of empowering women through Women Farmer Groups by using existing natural resources in the form of product management and marketing cultivation for the tourism development process in Sumbersari Village from available land. Now, Sumbersari Village, which is in the Wonolopo region, has taken the initiative to produce vegetables and ornamental plants through the modern agricultural market. With the synergy of the Independent Real Work Lecture at Wahid Hasyim University, with the empowerment of women from the Women Farmers Group, residents of Sumbersari Village, Wonolopo Sub-District are motivated to build and develop motivation and creativity to build villages to end stunting and create prosperity for village communities.